1986
DOI: 10.1083/jcb.102.2.510
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic exposure and recycling of membrane antigens of chromaffin granules: ultrastructural evaluation after immunolabeling.

Abstract: Abstract. The exocytotic exposure and retrieval of an antigen of chromaffin granule membranes were studied with chromaffin cells isolated from bovine adrenal medulla. Cells were incubated with an antiserum against glycoprotein III followed by fluorescein-or gold-labeled anti-IgG. Immunofluorescence on the cell surface was present in a patchy distribution irrespective of whether bivalent antibodies or Fab fragments were used. During subsequent incubation these fluorescent membrane patches were internalized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
117
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 29 publications
13
117
0
1
Order By: Relevance
“…These data are consistent with a freeze-fracture study that suggested the fused chromaffin granule membrane remains a distinct entity in the plasma membrane (11). Immunoelectron microscopy detected formation of clathrin-coated pits and vesicles containing glycoprotein III within 15 min of stimulation, but the spatial relationship to exocytotic sites could not be determined (8).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…These data are consistent with a freeze-fracture study that suggested the fused chromaffin granule membrane remains a distinct entity in the plasma membrane (11). Immunoelectron microscopy detected formation of clathrin-coated pits and vesicles containing glycoprotein III within 15 min of stimulation, but the spatial relationship to exocytotic sites could not be determined (8).…”
supporting
confidence: 80%
“…After 6 h, glycoprotein III was again found in large dense core granules. The antigen was also detected in vesicles close to but not within Golgi stacks (8). Second, biotinylation of exposed DBH upon chromaffin granule fusion demonstrated that DBH had not degraded after 24 h and was associated with another granule membrane, protein cytochrome b561 (39).…”
Section: Subsequent Fate Of the Secretory Granule Membranementioning
confidence: 92%
See 1 more Smart Citation
“…However, endocytosis presumably functions to retrieve LDCV membrane proteins after exocytosis. Indeed, the LDCV proteins glycoprotein III and ICA512 reappear in secretory granules after exposure at the cell surface (13,14).…”
mentioning
confidence: 99%
“…Sporadic evidence of functional recycling (retrieval and reuse) of secretory granule membrane proteins has been collected over the last 2 decades. In chromaffin cells, stimulation of secretion causes internalization of glycoprotein III/clusterin and dopamine ␤-hydroxylase from the plasma membrane and their subsequent re-entry into secretory granules (2)(3)(4). In insulinoma cells, stimulated secretion resulted in the endocytosis of two secretory granule membrane proteins, phogrin and ICA512, and their re-entry into newly forming insulin granules (5,6).…”
mentioning
confidence: 99%